INTEGRASI NILAI-NILAI PENDIDIKAN ISLAM WASAṬIYYAH MELALUI BUDAYA MODERASI BERAGAMA SEBAGAI UPAYA UNTUK MENINGKATKAN KERUKUNAN DAN TOLERANSI UMAT BERAGAMA DI KEBOMAS GRESIK - Mohammad Ahyan Yusuf Sya'bani; Yasa Griya Sejati; Ayu Fitri Fatmawati (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
The region, which is the center of industry and trade, makes Gresik increasingly crowded and complicated. On the other hand, Gresik is a city of culture and guardian city, which reflects in the cultural behavior and customs of its people in preserving the legacy of their predecessors from both religious and traditional issues. Included in this case is the village of Giri, Kebomas sub-district, the area affected. In this case, the Head of Muhammadiyah Youth Branch (PCPM) Kebomas, who lives in this area, feels that he is in a comfort zone with Gresik population, including the villages of Giri and Kebomas, which are predominantly Muslim. The PCPM Kebomas organization carries out its various activities in the scope of only one religion and even internal organizations; it has never touched across Muslim organizations, let alone interfaith organizations. Also, the relationship or coverage of the Kebomas PCPMnetwork with the dynamics of the outside world organization is minimal. The purpose of this service program is the realization of religious and Islamic moderation culture behavior inWasaṭiyyah through education for all members and leaders of PCPM Kebomas and the community in general in KebomasGresik. Efforts to integrate Wasaṭiyyah Islamic educational values to increase harmony and tolerance of religious communities.